Factors influencing engagement with adherence-enhancing mobile health app in sickle cell disease - Christina M Abrams; Natalia Davila; Sherif M Badawy; Shanon Marks; Maura M Kepper; Robert W Gibson; Allison A King; Victor R Gordeuk; Chinonyelum Nwosu; Sophie Li; Jeffrey A Glassberg; Lisa M Klesges; et al. (BMC Digital Health)
Abstract Background Mobile health (mHealth) applications have been utilized in chronic diseases to improve medication adherence, though factors driving engagement remain understudied. We previously demonstrated the benefits of mHealth app utilization in increasing adherence to hydroxyurea. In the “Integration of mHealth into Sickle Cell Disease (SCD) Care to Increase Hydroxyurea Utilization” (meSH) study, greater engagement with the InCharge Health app increased the percentage of days covered (PDC) for hydroxyurea. However, factors influencing app engagement were not investigated. This study aimed to identify patient-level factors associated with mHealth engagement during and post-study among adolescents and adults with SCD. Methods All meSH participants were included. The InCharge Health app use was measured for 24 weeks (study period) and 12 weeks (post-study period). Baseline demographics and validated measures of self-efficacy, financial hardship, and pain severity, impact, and frequency were evaluated as predictors of app engagement during the study period and post-study using linear models. Results Complete app use data were obtained from 284 of 293 participants, including 150 (52.8%) females and 240 (84.8%) who were HbSS/HbSβ0-thalassemia with a median age of 27 years. During the study period, 232 (81.7%) used InCharge Health at least once (median use excluding zeros: 26 days; IQR: 7–72 days). During the post-study period, 132 (46.5%) participants used the app at least once (median use excluding zeros: 16 days; IQR: 3–44 days). During the study period, the HbSS genotype, age > 25 years, higher education, higher self-efficacy score, and lower pain severity were associated with greater app engagement. Only age (p = 0.0032) and financial hardship (p = 0.0125) were significant in a multivariable model after backward elimination. During the post-study period, older age (p = 0.035), lower pain severity (p = 0.021) and lower frequency of pain (p = 0.033) predicted mHealth engagement. All three remained significant in a multivariable model after backward elimination. Conclusions Older age, lower financial hardship, lower pain severity, and greater self-efficacy were associated with increased engagement with a mHealth intervention for improving medication adherence among people living with SCD. This research can shift future app development from focusing on factors that drive patient interaction with mHealth targeting modifiable factors influencing app engagement. Trial registration The trial was registered with ClinicalTrials.gov. Registration Identifier: NCT04080167. Registration date: November 11, 2019.